Alfalfa (Medicago Sativa L.): Genotypic Diversity and Transgenic Alfalfa for Phytoremediation - Tussipkan, Dilnur; Manabayeva, Shuga A. (Frontiers in Environmental Science, 2022)
Soil contamination caused by industrial and agricultural activities is an environmental problem that poses a serious risk to human health and the ecosystem. Persistent organic pollutants (POPs) are organic chemicals that persist in the environment for long periods because of their high resistance to photolytic, chemical, and biological degradation. Besides POPs, high concentrations of non-essential heavy metals and metalloids, such as arsenic, cadmium, and lead, are increasingly becoming a problem worldwide. Remediation strategies for organic and inorganic pollutants in the environment have received global attention. For organic or inorganic contaminants, phytoremediation is the strategy of choice because of a green technology that uses plants and solar energy to clean hyper-accumulated toxic pollutants from the environment. Some plant species have a high capacity to grow and survive in elevated levels of contaminants. With a long cultivation history and adaptability to a wide range of territories, alfalfa has not only widely been used for animal feed and a medicinal herb but is also an ideal natural resource and model plant for remediation of contaminated soils, offering a variety of elite characteristics. This review provides firstly abundant genomic information on the genetic diversity and population structure of alfalfa. Secondly, we focused on the transgenic alfalfa plants for enhanced phytoremediation of POPs, such as atrazine, polychlorinated biphenyl (PCB), and trichloroethylene (TCE), as well as phytoremediation of petroleum and heavy metals. Thirdly, the future perspective of enhancement of phytoremediation efficiency was discussed in depth. This review is intended to provide a comprehensive overview of the phytoremediation capabilities of transgenic alfalfa plants, presenting fundamental information for future research studies for enhancing phytoremediation efficiency.